Type II diabetes mellitus and menopause: a multinational study. (December 2013) - Monterrosa-Castro, A.; Blümel, J. E.; Portela-Buelvas, K.; Mezones-Holguín, E.; Barón, G.; Bencosme, A.; Benítez, Z.; Bravo, L. M.; Calle, A.; Chedraui, P.; Flores, D.; Espinoza, M. T.; et al.
Abstract Background Type II diabetes mellitus causes metabolic changes that may lead to early menopause and worsen climacteric symptoms. Objectives To determine the risk factors for type II diabetes mellitus and assess the impact of this disease on the age of menopause and on climacteric symptoms. Methods A total of 6079 women aged between 40 and 59 years from 11 Latin American countries were requested to answer the Menopause Rating Scale and Goldberg Anxiety-Depression Scale. Results The prevalence of diabetes was 6.7%. Diabetes mellitus was associated with arterial hypertension (odds ratio (OR) 4.49; 95% confidence interval (CI) 3.47–5.31), the use of psychotropic drugs (OR 1.54; 95% CI 1.22–1.94), hormonal therapy (OR 1.46; 95% CI 1.11–1.92), ≥ 50 years of age (OR 1.48; 95% CI 1.17–1.86), overweight or obese (OR 1.47; 95% CI 1.15–1.89), and waist circumference ≥ 88 cm (OR 1.32; 95% CI 1.06–1.65). Factors associated with lower risk of diabetes were the use of hormonal contraceptives (OR 0.55; 95% CI 0.35–0.87), alcohol (OR 0.73; 95% CI 0.54–0.98) and living in cities > 2500 meters above sea level (OR 0.70; 95% CI 0.53–0.91) or with high temperatures (OR 0.67; 95% CI 0.51–0.88). In turn, diabetes tripled the risk of menopause in women under 45 years of age. Diabetes did not increase the risk of deterioration of quality of life due to climacteric symptoms. Conclusion Menopause does not increase the risk of type II diabetes mellitus. Diabetes is associated with early menopause in women under 45 years of age.